2022
DOI: 10.1126/science.abm1638
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial remodeling and ischemic protection by G protein–coupled receptor 35 agonists

Abstract: Kynurenic acid (KynA) is tissue protective in cardiac, cerebral, renal, and retinal ischemia models, but the mechanism is unknown. KynA can bind to multiple receptors, including the aryl hydrocarbon receptor, the a7 nicotinic acetylcholine receptor (a7nAChR), multiple ionotropic glutamate receptors, and the orphan G protein–coupled receptor GPR35. Here, we show that GPR35 activation was necessary and sufficient for ischemic protection by KynA. When bound by KynA, GPR35 activated G i - a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 75 publications
3
56
1
Order By: Relevance
“…It also inhibits CD4 + cell differentiation to the Th17 phenotype via AHR ( Wirthgen et al, 2018 ; Walczak et al, 2020a , b ) and is an endogenous activator of GPR35 ( Wang et al, 2006 ; Mackenzie and Milligan, 2015 ; Resta et al, 2016 ; Figure 2 ). This may carry novel implications for understanding the roles of kynurenic acid as new consequences of GPR35 activation are discovered such as those involving mitochondrial functioning ( Wyant et al, 2022 ).…”
Section: An Integrated Kynurenine-cytokine Systemmentioning
confidence: 99%
“…It also inhibits CD4 + cell differentiation to the Th17 phenotype via AHR ( Wirthgen et al, 2018 ; Walczak et al, 2020a , b ) and is an endogenous activator of GPR35 ( Wang et al, 2006 ; Mackenzie and Milligan, 2015 ; Resta et al, 2016 ; Figure 2 ). This may carry novel implications for understanding the roles of kynurenic acid as new consequences of GPR35 activation are discovered such as those involving mitochondrial functioning ( Wyant et al, 2022 ).…”
Section: An Integrated Kynurenine-cytokine Systemmentioning
confidence: 99%
“…In fact, reducing tryptophan intake is tantamount to reducing protein intake, which is all the more complicated as patients often already have protein intakes below the recommended level (1.2 g/kg/d) [30]. In addition, Wyant et al recently identified another tryptophan-derived UT, kynurenic acid, which plays a protective role against ischemia [31]. Reduced tryptophan intake could lead to a decrease in kynurenic acid and worsen ischemic disease, which is a major complication of CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a number of potential KynA receptors have been reported in the literature ( 113 119 ). We showed that ischemic protection by KynA reflects its ability to activate the orphan receptor GPR35 ( 120 ). Once bound to KynA, GPR35 internalizes to mitochondria where, in an ATPIF1-dependent manner, it promotes the dimerization of ATP synthase and thereby prevents futile ATP consumption by ATP synthase under hypoxic conditions ( 120 ).…”
Section: Remote Ischemic Protectionmentioning
confidence: 99%